O legado grego na terminologia gramatical brasileira - Neves, Maria Helena De Moura [UNESP] (Universidade Estadual Paulista Júlio de Mesquita Filho, 2011)
This study aims at investigating the existence of a Greek terminological legacy in the Brazilian grammatical organization, taking into account that the initial Greek grammar is the source of our grammar, through the Latin grammar, and that the field defined by it is a reference point for studying the evolution of Western thought about language. The theoretical and methodological approach is based on Historical Linguistics along the lines that guided the extensive research on the emergence of grammar in the West, which is the source of the information organized here (NEVES, 2005). The reflections focus on the examination of nomenclature, considering that it conceptually maps the set of positions assumed, and in general maintained, that deserve consideration. Among other things, the survey compared both Greek terms inherited in the continuous current of the grammatical thinking with Greek terms introduced later, and terms transliterated from the Greek with terms modeled on the Latin translation. In addition, there have been cases of names that were changed while the concept was kept and cases of concepts that were changed while the name was kept. Anyway, the examination of the nomenclature reveals the undeniable existence of a Greek legacy in the organization of the Portuguese grammar.

Este estudo tem como objetivo pesquisar a existência de um legado grego terminológico na organização gramatical brasileira, considerando que a gramática incipiente grega é a fonte da nossa gramática, por via da gramática latina, e que o recorte de campo que ela preparou é um ponto de referência para o estudo da evolução do pensamento ocidental sobre a linguagem. A orientação teórico-metodológica se assenta na Linguística Histórica, na linha que orientou a ampla pesquisa sobre a emergência da gramática no Ocidente que constitui a fonte das informações que aqui se organizam (NEVES, 2005). As reflexões dirigem-se especialmente para o exame da nomenclatura, entendendo que ela mapeia conceptualmente o conjunto das posições assumidas, e em geral mantidas, que merecem apreciação. Entre outras coisas o exame opôs: termos gregos legados na corrente contínua do pensamento gramatical a termos gregos introduzidos posteriormente; termos transliterados do grego a termos decalcados da tradução latina. Além disso, verificaram-se casos de alteração de nome com manutenção de conceito, e casos de alteração de conceito para um nome conservado. De todo modo, o exame da nomenclatura revela a indiscutível existência de um legado grego à organização da gramática portuguesa.
The legacy of Greek in the Brazilian grammatical terminology
Keywords: Brazilian grammatical nomenclature; Alexandrian grammar; Western grammar; Nomenclatura gramatical brasileira; Gramática alexandrina; Gramática ocidental